On the uniqueness conditions of solution of Bellman’s equation - Grigelionis, B. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. Об условиях единственности решения уравнения Беллмана B. Grigelionis. Apie Belmano lygties sprendinio vienatinumo sąlygas